Analytical study of the highest height of the player and the ball according to some biokinematic variables of the approximate run of the skill performance of spiking with a volleyball - M. Ahmed Alhamrani, Ali. (International Journal of Psychosocial Rehabilitation, 2020)
The importance of research in the study of high player and the ball according to the steps approximate the skill of beating crushing the ball plane to get to the number of appropriate steps with a high ball for a disease skill beating overwhelming study aimed to: 1. Identify Bio cinematics variables for a high ball and the player depending on the number of steps for the skill of beating overwhelming. 2. Identify the optimal number of steps in the kinematic variables for spiking for each player. As for the research procedures: The researcher used the descriptive approach The research sample consisted of 5 captain players from the team of Al-Mustansiriya University participating in the Iraqi Universities Championship in Kirkuk 2018, which was chosen by the deliberate method . The study variables were determined, and the overwhelming tests were conducted (one step, two steps, 3 steps), filmed, analyzed and recorded data for each player. The results were processed by the statistical packages. The following conclusions were reached: 1. Most of the players relied on increasing the height to jump on increasing the preparatory speed by increasing the number of steps, especially the first player. 2. It cannot be asserted openly that the greater the number of preparatory steps (the approximate run) for the jump, the greater the height of the jump because some players mainly rely on bending and extending (upward thrust) and increasing the starting angle in the vertical direction.